2014
DOI: 10.1039/c4cc00180j
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-confined GaN nanoparticles synthesized via liquid-ammonia-in-oil-microemulsions

Abstract: GaN nanoparticles, 3-4 nm in size, are synthesized in a microemulsion using liquid ammonia as the polar droplet phase. Surprisingly, GaN is readily crystalline although prepared at -40 °C. The nanoparticles show a band gap of 4.4 eV as well as light emission with its maximum at 336 nm. Both confirm the expected quantum-confinement effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…[104] Moreover,MEs using ionic liquids as the polar droplet phase have been described recently. [104,107] Their potential and current limitations are discussed in the following. As an additional restriction, the presence of small amounts of water cannot very often be excluded.…”
Section: Hydrogen Peroxide and Liquid Ammonia Based Microemulsionsmentioning
confidence: 99%
“…[104] Moreover,MEs using ionic liquids as the polar droplet phase have been described recently. [104,107] Their potential and current limitations are discussed in the following. As an additional restriction, the presence of small amounts of water cannot very often be excluded.…”
Section: Hydrogen Peroxide and Liquid Ammonia Based Microemulsionsmentioning
confidence: 99%
“…The large blue shift on the PL emission implies strong quantum confinement effects in GaN-NCs due to ultrasmall NCs generation (i.e., smaller than the doubled exciton Bohr radius for GaN (Ramvall et al 1998) using fs PLA (Miyamura et al 2002;Mazumder and Hector 2008). Gyger et al (2014) observed blue shift of 1.1 eV in PL spectra of 3-4 nm size GaN-NCs compared to band gap energy of bulk GaN. When GaN crystals become clusters, there are several effects which may change the band gap according to some theoretical studies and calculations (Brus 1986;Kayanuma 1988;Yoffe 2002;Dimos et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Development of GaN-based blue light emission devices (e.g., light-emitting diodes and laser diodes) (Nakamura et al 1991(Nakamura et al , 1996Denbaars 1997) accelerated the research on GaN. By limiting the size of a material to smaller than the doubled exciton Bohr radius, the material starts showing novel optical and structural properties like blue shift in optical absorption and PL spectra in comparison with the band gap emission of bulk material (Ramvall et al 1998;Gyger et al 2014). Crystalline GaN quantum dots provide enhanced carrier confinement-induced blue shift (Leppert et al 1998;Mićić et al 1999;Klimov et al 2000;Preschilla et al 2000;Miyamura et al 2002) and allow one to design core-shell nanostructures (Reiss et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations